미세입자의 트라이볼로지적 응용을 위한 마찰특성 고찰 - 성인하; 한흥구; 공호성 (한국트라이볼로지학회, 2009)
Interests in micro/nano-particles have been greatly increasing due to their wide applications in various fields such as environmental and medical sciences as well as engineering. In order to obtain a fundamental understanding of the tribological characteristics at particle-surface contact interface, frictional behaviors according to load/pressure and materials were obtained by using atomic force microscope (AFM) cantilevers with different stiffnesses and tips. Lateral contact stiffnesses were observed in various tip-surface contact situations. Experimental results show that stick-slip friction behavior occurs even when the colloidal probes with a particle of a few micrometers in diameter, which have a relatively large contact area and lack a well-shaped apex, were used. This indicates that atomic stick-slip friction may be a more common phenomenon than it is currently thought to be. Also, experimental results were investigated by considering the competition between the stiffness of the interatomic potential across the interface and the elastic stiffnesses of the contacting materials and the force sensor itself.